Research fronts regarding employees’ perception of HRM practices : https://doi.org/10.5937/etp2501039J - Jolović, Ivana; Jolović, Nevena (Ekonomija - teorija i praksa, 2025)
Crafted to effectively manage and optimize human capital in organizations, HRM practices bolster organizational objectives and improve entity prosperity and sustainability. These practices combine strategic foresight, supportive leadership, and innovative solutions to create a harmonious and thriving work environment. The foundational premise for this research is the cognition that HRM practices’ perceptions by "human" constituents of an organization may differ greatly. The conducted study chose to focus solely on employees’ interpretations of HRM practices (omitting the managerial perspective), simultaneously discussing HRM practices in bundles (transcending the limitations of the "isolated practice-centric" literature approach). The research aims to advance HRM theory in the previously mentioned field by integrating current knowledge, as there are very few recent studies doing so. The paper provides a critical, qualitative, and comparative review of the HRM practices research literature by analyzing thirty-three peer-reviewed studies published in a dozen international journals from 2019 to 2024. To gain credible holistic literature synthesis, the journal list primarily consisted of reputable, highly ranked journals known for their influential research history and substantial impact on HRM knowledge. The main research finding is a comprehension that HRM practices are not merely administrative routines but transformative tools that can alter employee behavior whilst elevating organizational performance and effectiveness in tandem.